Analisis Positioning Politik Partai NasDem Pada Pemilu 2019 di Kota Banda Aceh - Deo Muhammad Saad H; Ubaidullah, M.A (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2021)
The NasDem Party in Banda Aceh City experienced a degradation in the acquisition of votes and seats as a result of the bad image of the choice of the National NasDem Party coalition that supported Jokowi-Ma'ruf. This study aims to determine the political positioning of the NasDem Party in the 2019 Election in the City of Banda Aceh and its impact on the degradation of votes and seats for the DPRK NasDem Party in the 2019 Pemilu Legislatif. Theories used to analyze this problem are political positioning and political communication theory. The research method used is a descriptive-qualitative approach. The results of this study indicate that the Banda Aceh City NasDem Party experienced a political tsunami in the 2019 Election in Banda Aceh City, even the community from the start did not accept the presence of the NasDem party. Of course, it greatly affects the electability of candidates. This becomes the result of voter segmentation and is used as a reference by candidates in the campaign. The political communication strategy is carried out by the legislative candidates, with the condition that they do not carry the name of the NasDem Party during the campaign. The candidates are Heri Julius, Abdul Rafur and Daniel Abdul Wahab. The three of them received votes and seats in the Banda Aceh City DPRK 2019-2024 for the political positioning strategy carried out after obtaining identification of the criteria for the voter segment in Banda Aceh City. In the end, the Banda Aceh City NasDem Party as an institution did not have electability, but the candidates managed to increase their electability on their own. In contrast to the 2014 Pemilu Legislatif which was fully influenced by the electability of the NasDem Party, whereas the 2019 Pemilu Legislatif was fully influenced by the electability of candidates from the results of the political positioning strategy and political communication.Keywords: Banda Aceh City NasDem Party, Degradation of Votes and Seats, Political Positioning and Political Communication.